Lacticaseibacillus rhamnosus Hao9 exerts antidiabetic effects by regulating gut microbiome, glucagon metabolism, and insulin levels in type 2 diabetic mice - Han, Mei; Liao, Wenyan; Dong, Yao; Bai, Chen; Gai, Zhonghui (Frontiers in Nutrition, 2023)
Type 2 diabetes mellitus (T2DM) is a metabolic disease that has led to a significant global public health burden. In this work, we investigated the effects of Lacticaseibacillus rhamnosus Hao9 on T2DM in mice with high-fat diet- and streptozotocin (STZ)-induced diabetes (diabetic mice) and explored the underlying mechanisms. We found that 109 colony forming units (CFUs) of Hao9 per day significantly reduced fasting blood glucose levels and insulin resistance in diabetic mice. Moreover, Hao9 enhanced liver antioxidant capacity and significantly decreased glucose-6-phosphatase and phosphoenolpyruvate carboxykinase expression in the livers of diabetic mice. Hao9 also reduced the serum concentrations of pro-inflammatory cytokines and improved intestinal barrier function in diabetic mice. The composition of the gut microbiome was modulated by Hao9, with an increased abundance of Roseburia, Eubacterium, and Lacticaseibacillus, and decreased abundance of Escherichia/Shigella. Notably, Lacticaseibacillus was detected at both weeks 5 and 12 post-treatment, suggesting sustained colonization of the gut by Hao9. Overall, the beneficial effects of Hao9 supplementation on T2DM may be mediated by enhanced hepatic glucose metabolism and modulation of the gut microbiome. Therefore, Hao9 is a promising dietary supplement for the treatment of T2DM.